Formulation And Physical Quality Test Of Handsanitizer Gel PreparationOf Katuk Leaf Extract(Sauropus androgynus L.) With Gelling Agent Variations - Puteri Shinta; Shinta Mayasari; Aliyah Purwanti (LPPM Universitas dr. Soebandi, 2025)
Background: Diarrhea is one of the diseases caused by bacterial microorganism infections. Data obtained in 2023 showed that diarrhea cases increased to 27,385 diarrhea patients. Along with the times, people prefer instant and practical products as waterless hand sanitizers known as hand sanitizers. One of the important factors in the formulation of hand sanitizer gel preparations is the gelling agent to see the effect on the physical quality of the preparation. Objective: This study aims to formulate a hand sanitizer gel preparation of katuk leaf extract and evaluate its physical quality test with variations of the gelling agents Carbopol, CMC-Na, and HPMC. Method: This type of research is experimental research in the laboratory. This study uses katuk leaf extract as the active ingredient. Katuk leaf extract is obtained by maceration method with 96% ethanol solvent. The variations of gelling agents used in this study are carbopol, CMC-Na, and HPMC. The resulting handssanitizer gel preparations were tested for organoleptic, homogeneity, pH, dispersability and viscosity, respectively. Results: Katuk leaf extract can be formulated as a gel preparation of hand sanitizer of katuk leaf extract. The preparation of katuk leaf extract hand sanitizer gel with HPMC gelling agent has a thick texture, green, homogeneous gel form, pH 7,530.06, dispersion capacity of 4.75 cm0.69, and viscosity of 2.933251.66. Preparations with carbopol gelling agent have a gel form, have a thick texture, green color, homogeneous, pH 6,770.25, dispersion test 5.28 cm0.27, and viscosity of 3.033404.14. Preparations with CMC-Na gelling agent have a gel form, thick texture, green color, homogeneous, pH 6,970.06, dispersion test 5.17 cm0.03, and viscosity of 2.867251.66. Conclusion: Katuk leaf extract can be formulated as a gel preparation of hand sanitizer of katuk leaf extract. The evaluation of physical quality tests with variations of gelling agents that meet the standards of gel handssanitizer is from the gelling agent carbopol and CMC-Na, while HPMC does not meet the standards in terms of dispersion test.